ACCOUNTING PROVISIONS OF THE INVESTMENT COMPANY ACT. - Smith, Frank P. (The Accounting Review, 1941)
The U.S. Investment Company Act of 1940 brings one more branch of private finance within the fold of governmental regulation. The accounting provisions of the Investment Company Act do not ignore the specific weaknesses which were disclosed in the Securities and Exchange Commission's (SEC) study of the industry. The Act emphasizes the public aspects of investment company accounting and reporting practices and in most cases leaves to the SEC the drafting of definite standards to correct known weaknesses. Many of the sections of the Investment Company Act touch upon accounting practices and reports, and numerous financial practices are permitted only if certain tests are satisfactorily met. Such tests are usually based upon the results shown by accounting reports. The impression created by the accounting provisions of the Investment Company Act is that investment accounting and reporting standards are improving, and that the function of the SEC is first to bring the stragglers up to the minimum found adequate for investors, and then to encourage improvements. These aims will require numerous rules and regulations.